"Is it just so my right?" Women repossessing breastfeeding - Smith Paige (BMC, 2008)
Abstract Infant feeding occurs in the context of continued gender inequities and in the context of a feminist movement that left women vulnerable to a system that defined the male body and mind as the norm. This paper draws from a qualitative analysis of interviews conducted with women artists at the 2005 Mamapalooza music festival in New York City, and conference participants at the 2005 La Leche League International and International Lactation Consultant Association Conferences and at the 2007 Reproductive Freedom Conference to understand our collective alienation from breastfeeding and to outline a process for how we might repossess breastfeeding as a positive function in women's lives. These women find power in honoring and validating their own experiences, in claiming those experiences as legitimate feminist actions, and then drawing on these experiences to seek new meanings, customs and norms that similarly honor, value and support their rights to those experiences. They argue that we need a feminist movement that fully incorporates women's needs as biological and reproductive social beings, alongside their needs as productive beings, and a movement that defines the female body and mind as the norm.